No coma, but expressive dysphasia with cerebellar signs: an unique presentation of cerebral malaria - Shahar, Mohamed Arif; Ngiu, Chai Soon; Hashim, Hasnur Zaman; Tan, Hui Jang; Periyasamy, Petrick (Academy of Medicine, Singapore, 2011)
Malarial infection is not uncommonly complicated by cerebral involvement and poses significant mortality and morbidity especially in children. Similar complications may be seen in the adult population. Cerebral malaria is defined as encephalopathy that presents with impaired consciousness, delirium, and/or seizures. Neurological deficits are commonly seen as sequelae of cerebral malaria rather than as presenting symptoms or signs. We present here a unique case of cerebral malaria with focal neurological deficits but without alteration in conscious level. Keeping rare presentations of common illnesses in mind, clinicians should consider the possibility of cerebral malaria in a patient with neurological deficits and a history of fever and travel in endemic areas.